Zona Potensial Penyebaran Jaring Insang Dasar (Bottom Gill Net) di Perairan Kepulauan Sangkarrang - Ibnu Malkan Hasbi; Husni Angraeni; Ernawati Ernawati (Jurnal Airaha, 2020)
This study aims to determine the potential zone of Millenium Gill Net fishing gear which is scattered in the waters of the Sangkarrang Islands. The research was conducted in April-September 2019 in the waters of the Sangkarrang Islands District with a fishing base location of 5 ° 6'13.2664 "LS and 119 ° 25'59.2453" East Longitude. Data were collected by participating in fishing activities, observation and interviews with fishermen respondents. The catch coordinate data and the catch, besides that, the data is also obtained by downloading the ocean color in the form of sea surface temperature data and chlorophyll-a which is processed using the ArcGis map maker software. The research results obtained four points. First 5o2'15 "-5o2'55" LS and 119o24'30 "-119o25'0" East Longitude, Second 5o2'55 "-5o3'40" LS and 119o24'59 "-119o25'10" BT Third 5o5'7 "-5o5'52" LS and 119o23'35 "-119o24'0" East Longitude and the fourth 5o5'7 "-5o5'52" LS and 119o23'35 "-119o24'0" BT. For potential fishing zones I and II are dominated by outboard motor boats <1 gt while in potential zones III and IV 3 gt motor boats use basic gill nets.